Trichosanthes dioica Roxb.: An overview - Kumar, Nitin; Singh, Satyendra; M, Manvi; Gupta, Rajiv (Pharmacognosy Reviews, 2012)
Trichosanthes, a genus of family Cucurbitaceae, is an annual or perennial herb distributed in tropical Asia and Australia. Pointed gourd (Trichosanthes dioica Roxb.) is known by a common name of parwal and is cultivated mainly as a vegetable. Juice of leaves of T. dioica is used as tonic, febrifuge, in edema, alopecia, and in subacute cases of enlargement of liver. In Charaka Samhita, leaves and fruits find mention for treating alcoholism and jaundice. A lot of pharmacological work has been scientifically carried out on various parts of T. dioica, but some other traditionally important therapeutical uses are also remaining to proof till now scientifically. According to Ayurveda, leaves of the plant are used as antipyretic, diuretic, cardiotonic, laxative, antiulcer, etc. The various chemical constituents present in T. dioica are vitamin A, vitamin C, tannins, saponins, alkaloids, mixture of noval peptides, proteins tetra and pentacyclic triterpenes, etc.
Keywords: Cucurbitacin; diabetes; hepatoprotective; Trichosanthes dioica